2023
DOI: 10.3390/ijms24021408
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Treatment Augments Bioactive Phosphatidylethanolamine Concentrations in Kidney Cortex Membrane Fractions of Hypertensive Diabetic db/db Mice and Alters the Density of Lipid Rafts in Mouse Proximal Tubule Cells

Abstract: In addition to inhibiting renal glucose reabsorption and allowing for glucose excretion, the sodium/glucose cotransporter 2 (SGLT2) inhibitor dapagliflozin may be efficacious in treating various comorbidities associated with type 2 diabetes mellitus (T2DM). The molecular mechanisms by which dapagliflozin exerts its beneficial effects are largely unknown. We hypothesized dapagliflozin treatment in the diabetic kidney alters plasma membrane lipid composition, suppresses extracellular vesicle (EV) release from ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Decreased phosphatidylethanolamine content was reported in heart membranes isolated from streptozotocin-induced diabetic rats in combination with sarcolemmal Ca 2+ transport changes [ 65 ]. In accordance with our study, dapagliflozin increased phosphatidylethanolamine concentration in renal cortex membrane of diabetic mice [ 66 ]. On the other hand, SGLT2 inhibition decreased myocardial ceramide levels in Type 2 DM rats [ 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…Decreased phosphatidylethanolamine content was reported in heart membranes isolated from streptozotocin-induced diabetic rats in combination with sarcolemmal Ca 2+ transport changes [ 65 ]. In accordance with our study, dapagliflozin increased phosphatidylethanolamine concentration in renal cortex membrane of diabetic mice [ 66 ]. On the other hand, SGLT2 inhibition decreased myocardial ceramide levels in Type 2 DM rats [ 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…There are several strengths of this study. The cynomolgus monkey model of T2DM in the present study is a naturally occurring and clinically relevant experimental model that exhibits several characteristics frequently observed in diabetic patients including dyslipidemia 51,52 . Another strength is that, to our knowledge, this research was among the first to comparative analysis of fasting serum lipidomic profiles in T2DM cynomolgus monkeys combined untargeted and targeted lipidomics approaches.…”
Section: Discussionmentioning
confidence: 90%
“…The cynomolgus monkey model of T2DM in the present study is a naturally occurring and clinically relevant experimental model that exhibits several characteristics frequently observed in diabetic patients including dyslipidemia. 51,52 Another strength is that, to our knowledge, this research was among the first to comparative analysis of fasting serum lipidomic profiles in T2DM cynomolgus monkeys combined untargeted and targeted lipidomics approaches. Thus, the comparative analysis of serum lipidomics data to explore the associations between altered lipid profiles and the onset of T2DM not only provides insights into the pathophysiology of DM but also leads to the development of novel means of treating DM.…”
Section: Discussionmentioning
confidence: 99%
“… 122 Interestingly, research also found that SGLT2 inhibitor dapagliflozin treatment in db/db diabetic mice altered the concentration of membranous lipids in the kidney cortex based on mass spectrometry lipidomics. 123 The role of SGLT2 inhibitors in renal lipid regulation in the context of DKD was also supported by human study. A moderate size of prospective study demonstrated that diabetic patients treated with metformin and empagliflozin had lower advanced glycation end products levels and renal fat accumulation than those treated only with metformin.…”
Section: The Role Of Sodium‐glucose Transporter 2 Inhibitor In Renal ...mentioning
confidence: 86%